Effect of monthly vitamin D supplementation on antibiotic prescribing in older adults: a post hoc analysis of a randomized controlled trial. Issue 1 (19th March 2021) - Wu, Zhenqiang; Camargo, Carlos A; Sluyter, John; Waayer, Debbie; Toop, Les; Scragg, Robert
ABSTRACT: Background: Observational studies have reported that low vitamin D status is associated with increased risk of antibiotic use. However, trials on the effect of vitamin D supplementation on antibiotics are limited and inconclusive. Objectives: The main objective of this study was to determine the effect of monthly vitamin D supplementation on the proportion of adults with ≥1 prescriptions of antibiotics. The secondary outcomes were to determine the effect of monthly vitamin D supplementation on the number of antibiotic prescriptions and the number of days on antibiotics. Methods: This was a post hoc analysis of a randomized, double-blinded, placebo-controlled trial with community-based older adults who were randomly assigned to receive monthly 100, 000 IU of vitamin D or identical placebo. All analyses were based on the principle of "intention to treat." RR from log-binomial models and the incidence rate ratio (IRR) from negative binomial models were estimated for primary and secondary outcomes after adjusting for age, sex, and ethnicity. Results: A total of 5108 participants aged 50–84 y were randomly assigned to vitamin D supplementation ( n  = 2558) or placebo ( n  = 2550) groups. During a median follow-up of 3.3 y, 4211 (82%) participants were prescribed antibiotics. There was no difference in the proportion of participants prescribed antibiotics between vitamin D (82%) and placebo (83%) groups (adjusted RR: 0.99; 95% CI: 0.97, 1.01; P  = 0.42). Similarly, the number of antibiotic prescriptions per person-year did not differ between the 2 treatment groups (adjusted IRR: 0.98; 95% CI: 0.93, 1.04; P  = 0.58). However, the number of days on antibiotics per person-year was significantly lower in the vitamin D group (mean ± SEM: 15 ± 0.7) compared with the placebo group (mean ± SEM: 17 ± 0.8) (adjusted IRR: 0.90; 95% CI: 0.82, 0.98; P  = 0.01), especially for the tetracyclines (IRR: 0.65; 95% CI: 0.50, 0.85; P  = 0.002). Conclusions: Long-term, monthly, high-dose vitamin D3 supplementation did not prevent antibiotic prescribing in older adults, but the vitamin D group had fewer days per person-year on antibiotics. Further research is required to replicate these findings. This trial was registered at www.anzctr.org.au as ACTRN12611000402943.